Nonparametric test for spatial geometric anisotropy - Dučinskas, Kęstutis; Dreižienė, Lina (Lietuvos matematikos rinkinys, 2010)
Paper deals with a problem of testing isotropy against geometric anisotropy for Gaussian spatial data. The original simple test statistic based on directional empirical semivariograms is proposed. Under the assumption of independence of the classical semivariogram estimators and for increasing domain asymptotics, the distribution of test statistics is approximated by chi-squared distribution. The simulation experiments demonstrate the efficacy of the proposed test.